EFEKTIVITAS MEDIA KOMIK BERBANTUAN MODEL BERMAIN PERAN UNTUK PENINGKATAN KETERAMPILAN BERBICARA PADA SISWA KELAS V SD - Susanti, Lina Risti (Universitas Muria Kudus, 2023)
This study aims to determine the implementation of comics media with a role-playing model in speaking skills. This study is a solution to the low speaking skills of students. By using comic media with a role-playing model during learning, it brings an increase in student learning outcomes, especially speaking skills. The method used is a action research. The research findings show that comic media with role-playing model in speaking skills is very effective in improving the speaking skills of fifth grade students at SDN 3 Pelang.